Numerical Study of Temperature and Air Velocity Distribution In Oil Filling Factory - Hernawan Novianto; Prabowo Prabowo (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2017)
This paper describes the use of CFD modeling to analyze the thermal comfort in the oil filling factory which has an area of 3000 m2. The need for this analysis comes from an uncomfortable condition that is felt by the workers of the factory. A 3D simulation using FLUENT software 6.3.26 conducted to analyze the temperature and velocity distribution in the plant room. The water is assumed as an incompressible ideal gas, steady flow, turbulence models used k−